Proceedings of the 4th Workshop of Narrative Understanding (WNU2022) 2022
DOI: 10.18653/v1/2022.wnu-1.7
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Detection and Feature Analysis in Online Health Communities

Abstract: Narratives have been shown to be an effective way to communicate health risks and promote health behavior change, and given the growing amount of health information being shared on social media, it is crucial to study healthrelated narratives in social media. However, expert identification of a large number of narrative texts is a time consuming process, and larger scale studies on the use of narratives may be enabled through automatic text classification approaches. Prior work has demonstrated that automatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The results for all models on the test set are presented in Table 3. Our findings align with those of Ganti et al (2022), who found that transformer-based models consistently outperform bag-of-words models for narrative detection, with the fine-tuned base RoBERTa model performing best overall, outperforming even the version of RoBERTa pretrained specifically on Twitter data. The GPT-3 text-davinci-003 model achieved high precision but lacked in recall, resulting in an F1-score similar to the bag-of-words models, though it requires less than 1% of the amount of training data (in the form of examples for in-context learning).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results for all models on the test set are presented in Table 3. Our findings align with those of Ganti et al (2022), who found that transformer-based models consistently outperform bag-of-words models for narrative detection, with the fine-tuned base RoBERTa model performing best overall, outperforming even the version of RoBERTa pretrained specifically on Twitter data. The GPT-3 text-davinci-003 model achieved high precision but lacked in recall, resulting in an F1-score similar to the bag-of-words models, though it requires less than 1% of the amount of training data (in the form of examples for in-context learning).…”
Section: Resultssupporting
confidence: 88%
“…While most studies of narratives have relied on manual annotations, Dirkson et al (2019) and Verberne et al ( 2019) used human-assigned labels to train text classification models to detect narrativity in social media posts in the health domain. Both studies focused on bag-of-words models with ngram features, while more recent research found that deep learning models were more successful than classical machine learning models at detecting narratives in Facebook posts (Ganti et al, 2022). These studies suggest that automatic narrative classification could enable the labeling of even larger social media datasets.…”
Section: Related Workmentioning
confidence: 99%